Analysis and quantification of in vitro myoblast fusion using the LADD Multiple Stain - McColl, Rhys (BioTechniques, 2016)
Myoblast fusion, which is essential for muscle development, regeneration, and repair, can be assessed in vitro via the calculation of a fusion index. Traditionally, this requires use of either immunocytochemistry or fluorescently-labeled cytoskeletal staining, followed by microscopy and laborious analysis. The expense and time-consuming nature of the optimization and application of antibody-based techniques such as immunocytochemistry, as well as the need for specialized analytical equipment such as fluorescence microscopes, presents a barrier to the routine analysis of this crucial step during terminal differentiation. Here, we describe (i) a novel use of the commonly available LADD Multiple Stain for visualization of myoblast fusion in vitro; (ii) the optimization of a simple image analysis method to generate quick, quantifiable data representative of a fusion index; and (iii) the use of a protocol combining these two procedures to investigate in vitro myoblast fusion in a simple and efficient manner as proof-of-concept